Application and evaluation of hyper‐ and hypoelastic‐based plasticity models in the FE simulation of metal forming processes. Issue 1 (29th November 2013) - Brepols, Tim; Vladimirov, Ivaylo N.; Reese, Stefanie
Abstract: Metal forming processes are usually accompanied by large plastic strains and rotations of the material elements which emphasizes the need for reliable finite strain elastoplasticity models in corresponding FE simulations. In this work, two specific finite strain hyper‐ and hypoelastic‐based plasticity models with combined nonlinear isotropic and kinematic hardening are presented and compared in numerical FE simulations. Although both models led to remarkably different results in a shear‐dominated single element deformation test, the structural simulation of a standard deep drawing process delivered nearly congruent results which suggests that both models are equally well‐suited for modeling metals in common forming processes. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)